Analisa Rasio Kinerja Pada Perusahaan di Indonesia dengan Regresi Berganda - Pudjiono Pudjiono (Jurnal Ekonomika dan Manajemen, 2019)
This study aims to look at how the relationship between the ratio of the company's performance with other financial ratios on against disclosure of corporate social responsibility in real estate companies listed on the Indonesia stock exchange in 2011-2013 period by using multiple rgresi analysis is simple. The research of using multiple regression analysis method with its independent variable is the variable of CSR. From research performed at the pull of the conclusion that the ratio of the financial performance of companies in doing research significant effect, except for CR kinerja ratio (current ratio)